Panama : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
This Selected Issues paper focuses on background, challenges, and policy options in Panama. Panama stands at a crossroad between taking the leap to become an advanced economy or getting stuck in the middle-income trap. The beginning of a new administration provides a window of opportunity to initiate and implement ambitious reforms. This note takes stock of fiscal issues in Panama and proposes policy options. The new administration's fiscal agenda should feature a comprehensive reform of tax and customs administrations, a review of tax incentives and exemptions and consider steps toward a broader tax policy reform. Efforts to further strengthen the fiscal framework with the appointment of the members of the Fiscal Council should continue going forward. Panama should adopt best practice fiscal accounting and reporting methods. A comprehensive assessment and management of fiscal risks is necessary to create buffers and safeguard public finances given fiscal policy's exclusive stabilization role.